Anatomical Study of the Transverse Sections of stems, Leaves petioles and Lamina of Securigera DC. , Sophora L. and Taverniera DC. Genera Species (Leguminosae) in Iraq. - A.A., Susa.; Al-Kulaby, Z.Q.A. (Al-Qadisiyah Journal of Pure Science, 2018)
The current research was conducted anatomical study of the for Transverse Sections of stems, Leaves , petioles and Lamina for tayp genera species family (Leguminosae),and this genera are Securigera DC. ,Sophora L. and Taverniera DC. in Iraq, which included one species (Se .securidaca ) of the first genus and two species (So .gibbosa Ùˆ So .japonica) to second genus, and one species(T.nummularia ) for third genus. Studied the anatomical characteristics of Transverse Sections of stems, Lamina Leaves ,petioles to species of genera under study, it had some important characteristics value in isolation these species like isolation species Se .securidaca it has Hollow stems in some time was Sold in other species. also that shape of petiole was had important characteristics diagnosis as well as shape vascular bundle In stems and petiole at this point .and give Mesophyll tissue for leaval important in characteristics and strip the species under study and also it was density of Indumentum increased the important qualities in diagnosis and isolation.